2011
DOI: 10.1021/es2010545
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity and Metabolic Potential of Activated Sludge Microbial Communities in Full-Scale Wastewater Treatment Plants

Abstract: The activated sludge process is an essential process for treating domestic and industrial wastewaters in most wastewater treatment plants (WWTPs). This process consists of a mixture of general and special microorganisms in a form of a complex enrichment population. Thus, the exploration of activated sludge microbial communities is crucial to improve the performance of activated sludge process. In this study, we investigated the phylogenetic diversity and metabolic potential of activated sludge microbial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(84 citation statements)
references
References 69 publications
9
74
1
Order By: Relevance
“…Empirical and theoretical studies of macrobial systems have demonstrated that drift is most important when selection is weak, alpha diversity is low, and the total number of community members is small (reviewed in reference 54). These conditions can be met in certain types of microbial communities, including nutrient-rich systems such as wastewater treatment facilities (108,109) as well as host-associated environments (110). The vast majority of taxa in microbial communities are found in low relative abundances.…”
Section: Driftmentioning
confidence: 99%
“…Empirical and theoretical studies of macrobial systems have demonstrated that drift is most important when selection is weak, alpha diversity is low, and the total number of community members is small (reviewed in reference 54). These conditions can be met in certain types of microbial communities, including nutrient-rich systems such as wastewater treatment facilities (108,109) as well as host-associated environments (110). The vast majority of taxa in microbial communities are found in low relative abundances.…”
Section: Driftmentioning
confidence: 99%
“…However, little work has focused on the ecological consequences of press (that is, prolonged) disturbances on microbial diversity and the extent of compositional versus environmental effects on ecosystem function (Allison and Martiny, 2008). Most community ecology studies in activated sludge systems have been limited to microbial diversity surveys of fullscale municipal treatment plants that are not open to experimental manipulation (Wells et al, 2009(Wells et al, , 2011Yang et al, 2011;Ye et al, 2011;Zhang et al, 2012;Saunders et al, 2013). Thus, a large knowledge gap exists with regard to activated sludge microbial community temporal variability, responses to speciesselection pressures and resilience to disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the microbiological methods used, plenty of the studies on microbial communities of activated sludge bioreactors have been conducted to profile taxonomic information based on 16S rRNA genes, using technical approaches of clone library (Wells et al 2011;Yang et al 2011), denaturing gradient gel electrophoresis (DGGE) (Yang et al 2011), terminal restriction fragment length polymorphism (T-RELP) (Wells et al 2011;Yang et al 2011), fluorescence in situ hybridization (FISH) (Mielczarek et al 2012(Mielczarek et al , 2013, Illumina (Albertsen et al 2012), 454-pyrosequencing (Hu et al 2012;Wang et al 2012a), and PhyloChips (Xia et al 2010). However, 16S rRNA gene-based ways may not be efficient in distinguishing some closely related but ecologically distinct groups of microorganisms as a consequence of the low evolutionary rate of 16S rRNA genes (Palys et al 1997).…”
Section: Introductionmentioning
confidence: 99%